(untitled) (Journal of Computational Mathematics, 2021)
The multigrid algorithm in [13] is developed for solving nonlinear parabolic equations arising from the finite element discretization. The computational cost of the algorithm is approximate O(N_kN) where N_k is the dimension of the finite element space and N is the number of time steps.